Dual-tapered Mach Zehnder interferometer for dual-wavelength Q-switched YDFL using Molybdenum diselenide - Mat Salim, Muhammad Aizi (2023)
A dual-wavelength Q-switched YDFL by utilizing MoSe2 thin film was successfully achieved in cavity ring. The dual synchronous wavelength output spectrum centered at 1035.8nm to 1040.2nm was achieved with repetition rate of 15.3 kHz to 35.2 kHz. Moreover, the maximum pulse energy was 2.8nJ and minimum pulse width was 1.8μs. In this paper, MoSe2 thin film capabilities as saturable absorber in 1-micron region was successfully achieved. Thus pave a new insight of transition metal chalcogenides (TMD) based photonics device.